PEMANFAATAN VIRTUAL OFFICE DALAM MENINGKATKAN MANAJEMEN PERKULIAHAN (STUDI KASUS SEKOLAH TINGGI ILMU ADMINISTRASI SEBELAS APRIL SUMEDANG) - Maya Suhayati (JRPA - Journal of Regional Public Administration, 2016)
Class is one managerial activities are very important in an institution of higher learning. This is due to these activities involve interaction between faculty and students of academic institutions as well as the external environment. Lecturing activities manually in this case only face to face between lecturers and students already felt not very effective because there is always a factor that resulted bored lazy student to be actively involved. By using a virtual office system in this case using a computer and network media in the communication of the course such as using social networking media, classroom techniques and methods google drive or drive one expected the boundary between students and lecturers can be minimized so that effective communication can be achieved with good. Effective communication can improve management in lectures, in this case associated with low management, middle management and top management.